ASMT Regulates Tumor Metastasis Through the Circadian Clock System in Triple-Negative Breast Cancer - Xie, FenFen; Wang, LiLi; Liu, YaJing; Liu, ZhenBang; Zhang, ZuoYang; Pei, Jing; Wu, ZhengSheng; Zhai, MuXin; Cao, YunXia (Frontiers in Oncology, 2020)
Objective: Triple-negative (PR−, ER−, HER-2−) breast cancer (TNBC) is regarded as more aggressive and more likely to recur after medical care. Emerging evidence has demonstrated that the circadian clock system regulates cell-signaling pathways critical to cancer cell proliferation, survival and metastasis, meaning that it could be a good candidate for TNBC treatment. As such, the aim of the current study was to examine the molecular mechanism by which the circadian clock system contributes to cancer progression in TNBC. Methods: Cancer cells and primary breast cancer tissues were immunostained for the measurement of circadian clock proteins (CLOCK, BMAL1 and PER1) and acetylserotonin methyltransferase (ASMT). The association between ASMT and clock proteins was assessed using siRNA and Western blot. Transwell assays were used to detect cancer cell migration and invasion while MTT assays were utilized to evaluate cell proliferation. Results: Circadian clock proteins (CLOCK, BMAL1 and PER1) and ASMT expression were high in TNBC and triple positive breast cancer (TPBC) compared with para-carcinoma tissues (PCTs). Intriguingly, there was an obvious correlation between circadian clock proteins and ASMT expression in both TPBC and TNBC. Similarly, circadian clock proteins and ASMT were expressed to a greater extent in BT-474 (triple-positive) cells than in MDA-MB-231 (triple-negative) cells. The inhibition of ASMT reduced circadian clock protein levels in both breast cancer cell lines. Further analysis showed that the expression levels of ASMT and circadian clock proteins did not correlate with clinical parameters such as age, tumor size, histologic grade and CK5/6, but increased significantly with lymphatic invasion in TNBC. In agreement with this finding, knockdown of ASMT significantly leads to reductions in migration and invasion by downregulating clock expression in MDA-MB-231 cells.. Conclusion: Our study suggests that ASMT regulates the circadian clock system in breast cancer and inhibition of ASMT reduce the invasiveness of triple-negative breast cancer cells by downregulating clock protein in a certain extent, indicating the potential value of ASMT as a drug target for TNBC treatment.